Evaluation models and evaluation use - Contandriopoulos, Damien (2012)
The use of evaluation results is at the core of evaluation theory and practice. Major debates in the field have emphasized the importance of both the evaluator’s role and the evaluation process itself in fostering evaluation use. A recent systematic review of interventions aimed at influencing policy-making or organizational behavior through knowledge exchange offers a new perspective on evaluation use. We propose here a framework for better understanding the embedded relations between evaluation context, choice of an evaluation model and use of results. The article argues that the evaluation context presents conditions that affect both the appropriateness of the evaluation model implemented and the use of results.